Insights on the biochemical and cellular changes induced by heat stress in the Cladocopium isolated from coral Mussismilia braziliensis - Lima, Michele S.; Hamerski, Lidilhone; Silva, Tatiana A.; da Cruz, Maria Luíza R.; Varasteh, Tooba; Tschoeke, Diogo A.; Atella, Georgia C.; de Souza, Wanderley; Thompson, Fabiano L.; Thompson, Cristiane C. (Frontiers in Microbiology, 2022)
Corals are treatened by global warming. Bleaching is one immediate effect of global warming, resulting from the loss of photosynthetic endosymbiont dinoflagellates. Understanding host-symbiont associations are critical for assessing coral’s habitat requirements and its response to environmental changes. Cladocopium (formerly family Symbiodiniaceae clade C) are dominant endosymbionts in the reef-building coral, Mussismilia braziliensis. This study aimed to investigate the effect of temperature on the biochemical and cellular features of Cladocopium. Heat stress increased oxygen (O2) and decreased proteins, pigments (Chla + Chlc2), hexadecanoic acid- methyl ester, methyl stearate, and octadecenoic acid (Z)- methyl ester molecules. In addition, there was an increase in neutral lipids such as esterified cholesterol and a decrease in free fatty acids that may have been incorporated for the production of lipid droplets. Transmission electron microscopy (TEM) demonstrated that Cladocopium cells subjected to heat stress had thinner cell walls, deformation of chloroplasts, and increased lipid droplets after 3 days at 28°C. These findings indicate that thermal stress negatively affects isolated Cladocopium spp. from Mussismilia host coral.